Spatial Modeling for Urban Resilience Assessment: Using AHP and GIS (Case Study of Bou-Saâda City, Algeria) - Mayouf, Zouhair; Nouibat, Brahim (Technium Social Sciences Journal, 2022)
The aim of the research is spatial modeling to assess urban resilience. A group of Delphi experts were involved, in stages, to select the final criteria. Using Multi-Criteria Decision Analysis (MCDA) by (AHP), the final criteria were ranked according to weight and importance. Criteria maps within a GIS environment were combined with AHP results, to create an Urban Resilience Map (URM). The results showed that (52.19%) of the study area achieved high resilience, (30.86%) medium resilience and (16.95%) low resilience. The results also showed that there are differences between the neighborhoods of the city of Bou-Saâda in terms of resilience that can be determined spatially. The results of this research can be used as a decision aid such as providing suggestions to planners and managers in prioritizing their interventions (such as urban renewal of neighborhoods) by conducting checks on less resilience criteria, in order to support the city's ability to respond to shocks.